The influence of discipline and work abilities on employee performance in the assembling section of PT. Hilex Indonesia - Sabina, Fitri (Privietlab, 2024)
This research is quantitative research that uses methods based on the philosophy of positivism, with the aim of testing predetermined hypotheses. The measurement instrument in this research is an ordinal scale questionnaire with a Likert scale. The research population was 180 employees of the assembly section of PT Hi-lex Indonesia. The sampling technique used is Simple Random Sampling, using the Slovin formula to determine the number of samples. The calculation results show that the required sample size is 65 respondents. This research analysed the influence of discipline and workability on employee performance. The research results show that discipline and workability partially positively and significantly affect employee performance at PT. Hilex Indonesia. Workability received the highest score, indicating that ability is the dominant variable influencing employee performance. The analysis results also show that discipline and workability simultaneously positively and significantly affect employee performance by 78%. In comparison, the remaining 22% can be explained by other variables outside the research. From the results of the questionnaire description, the lowest variable of discipline is competence. Therefore, it is recommended that management train employees to improve their competence. Employee abilities also need to continue to be improved, and management is advised to provide additional motivation so that employee morale remains optimal.